Corporate entrepreneurship at the university: the influence of managerial support, autonomy and reward on the innovative behavior of university professors - Moraes, Gustavo Hermínio Salati Marcondes de; Spers, Eduardo Eugênio; Mendes, Luciano; Silva, Hermes Moretti Ribeiro da [UNESP] (Emerald, 2021)
Purpose: The study aims to analyze the influence of managerial support, autonomy and reward perception on the innovative behavior of university professors. Design/methodology/approach: Quantitative methodology based on partial least squares structural equation modeling. The sample obtained totaled 208 responses from professors at three public universities in the State of Sao Paulo, Brazil. Findings: The results indicate that managerial support is a fundamental factor for developing an organizational environment that is more conducive to innovative behavior and corporate entrepreneurship. However, in educational institutions with a more focused entrepreneurial ecosystem, it was discovered that reward perception is not a fundamental factor for the innovative behavior of university professors. Practical implications: From a practical perspective, academic institutions interested in stimulating corporate entrepreneurship should create opportunities for collaboration among professors to solve problems, encourage professors to expose their work beyond the university environment and improve the main indicators of management support and autonomy presented in this research. Social implications: The study presents indicators and implications, which are of particular interest for university managers and public policy writers. Originality/value: The study is demonstrably original. Through its unique analysis of the innovative behavior of university professors and the connections between variables in the university environment and its use of a robust modeling method in an emerging-economy context, the study furthers existing research by helping to understand why some firms are better than others at corporate entrepreneurship.
Keywords: Corporate entrepreneurship; Entrepreneurial ecosystem; Innovative behavior; Management support; University environment